1994
DOI: 10.1073/pnas.91.26.12373
|View full text |Cite
|
Sign up to set email alerts
|

Selective clustering of glutamate and gamma-aminobutyric acid receptors opposite terminals releasing the corresponding neurotransmitters.

Abstract: Several immunocytochemical and physiological studies have demonstrated a concentration of neurotransmitter receptors at postsynaptic sites on neurons, but an overall picture of receptor distribution has not emerged. In particular, it has not been clear whether receptor clusters are selectively localized opposite terminals that release the corresponding neurotransmitter. By using antibodies against the excitatory glutamate receptor subunit GluRl and the inhibitory type A yaminobutyric acid (GABA) receptor P2/3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
170
2
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(188 citation statements)
references
References 44 publications
(57 reference statements)
15
170
2
1
Order By: Relevance
“…Moreover, the α6 subunit was detected only within the synaptic glomeruli, where Golgi cell axons were innervated. These results supported that the previous report [9] and suggested that GABAergic synapse-formation might induce targeting of the receptor subunits to the synaptic site, and prevent retention in the cell bodies and axons in vivo.…”
Section: Regulatory Mechanism Underlying the Targeting And Accumulsupporting
confidence: 92%
“…Moreover, the α6 subunit was detected only within the synaptic glomeruli, where Golgi cell axons were innervated. These results supported that the previous report [9] and suggested that GABAergic synapse-formation might induce targeting of the receptor subunits to the synaptic site, and prevent retention in the cell bodies and axons in vivo.…”
Section: Regulatory Mechanism Underlying the Targeting And Accumulsupporting
confidence: 92%
“…Together with integrin-mediated astroglial adhesion to neurons, these prostaglandins activate protein kinase C signaling in neurons and excitatory synaptogenesis (Hama et al, 2004). Craig et al (1994) were the first to demonstrate Glu-R1 and GABA A receptors opposite their transmitter-release sites. AMPA-receptor clustering is induced by activity-dependent Narp (O'Brien et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate receptors are clustered in the post-synaptic density (PSD) opposite presynaptic terminals releasing glutamate (Craig, et al, 1994). This organization of the receptor is critical for efficient neurotransmission and is the product of a complex process involving trafficking and immobilization of receptors at the synapse.…”
Section: Nmda Receptor Trafficking and Synaptic Targetingmentioning
confidence: 99%